Assistance in the Cultivation of Stingless Bees and the Development of Derivative Products in Sungkai Green Park Ecotourism - Henny Herwina; Jasmi Jasmi; Eli Ratni; Afifah Putri; Atiqoh Rinjani Utami; Atthoriq Fauzan; Miftahul Ilmi; Ferdhinal Asful (Warta Pengabdian Andalas, 2024)
The practice of cultivating Galo-galo bees has been steadily developing each year in West Sumatra. All parts of the Galo-galo bee, from honey to propolis, can be effectively utilized to produce commercial products, thereby enhancing the community's economy. Community service activities at Sungkai Green Park Ecotourism (ESGP) in Lambung Bukit Village, Padang, assist the community in cultivating Galo-galo bees. These activities involved providing colonies, conducting socialization sessions, offering mentoring and discussions, and collecting data on local plants and insects. Additionally, knowledge regarding the use and processing of honey and propolis was shared. These community service activities, conducted from September to December 2023, have had a positive impact, particularly on the community around the ESGP area. This aligns with the goal of the initiative, which is to provide education and hands-on practice in Galo-galo bee cultivation.